2011
DOI: 10.1371/journal.ppat.1002082
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan Binding Facilitates Entry of a Bacterial Pathogen into Central Nervous Systems

Abstract: Certain microbes invade brain microvascular endothelial cells (BMECs) to breach the blood-brain barrier (BBB) and establish central nervous system (CNS) infection. Here we use the leading meningitis pathogen group B Streptococcus (GBS) together with insect and mammalian infection models to probe a potential role of glycosaminoglycan (GAG) interactions in the pathogenesis of CNS entry. Site-directed mutagenesis of a GAG-binding domain of the surface GBS alpha C protein impeded GBS penetration of the Drosophila … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 65 publications
1
51
0
Order By: Relevance
“…Similarly, fibronectin bridges N. meningitidis to a 5 b 1 integrin on BMEC surface enabling bacterial internalization (Unkmeir et al 2002). Glycan structures, specially glucosaminoglycans (GAG), that interact with integrin signaling machinery, have been shown to interact with bacterial proteins such as the GBS a C protein (Chang et al 2011). Given that many of these host cell factors preferentially localize to the basolateral surface of polarized endothelium, disruption of junctional protein complexes on infection may result in a nonpolarized distribution of proteins on the BBB plasma membrane and their luminal accessibility (see below).…”
Section: Microbial Adhesion To Bmec and Transcytosis Across The Bbbmentioning
confidence: 99%
“…Similarly, fibronectin bridges N. meningitidis to a 5 b 1 integrin on BMEC surface enabling bacterial internalization (Unkmeir et al 2002). Glycan structures, specially glucosaminoglycans (GAG), that interact with integrin signaling machinery, have been shown to interact with bacterial proteins such as the GBS a C protein (Chang et al 2011). Given that many of these host cell factors preferentially localize to the basolateral surface of polarized endothelium, disruption of junctional protein complexes on infection may result in a nonpolarized distribution of proteins on the BBB plasma membrane and their luminal accessibility (see below).…”
Section: Microbial Adhesion To Bmec and Transcytosis Across The Bbbmentioning
confidence: 99%
“…Streptococcus agalactiae penetrates the BBB via interactions between bacterial surface alpha C protein and host surface heparan sulfate chains [19]. It has been shown that heparan sulfate and heparin are defined by similar underlying backbones (GlcNAcα1-4GlcAβ1-4/IdoAα1-4) n , though heparin undergoes more extensive sulfation and uronic acid epimerization [20].…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial association with and invasion into hBMECs or the human alveolar cell line A549 were quantified as previously described, with minor modifications [12,19,26,52]. hBMECs or A549 cells were seeded at 2 × 10 5 cells into 24-well plates 1 day prior to bacterial infection.…”
Section: Methodsmentioning
confidence: 99%
“…We showed previously that genetic impairment of HS expression in flies or mice reduced GBS dissemination into the brain (24). To examine how altering 2-O-sulfation might influence susceptibility to GBS meningitis, we measured GBS dissemination into brain after intravenous challenge (Fig.…”
Section: Resultsmentioning
confidence: 99%